Komparasi Agribisnis Jamur Tiram (Pleurotus ostreatus) Media Tanam Limbah Sabut Kelapa dan Serbuk Gergaji - Heryadi, D Yadi; Sundari, Ristina Siti; Agustini, Rini; Hidayat, Andang (Kadiri University, 2021)
The agribusiness of oyster mushrooms (Pleurotus ostreatus) is getting interested due to an increase in demand. It has almost complete nutrients, high protein content that can substitute animal protein for vegetarians. The growth medium for oyster mushrooms commonly uses sawdust. The cocopeat waste medium is an innovation. The research descriptively compares production cost, yield, revenue, income, and feasibility throughout both mediums. Findings that the total cost of sawdust medium was higher 750,000IDR than cocopeat waste. In terms of income, sawdust medium earned 140.72%, while cocopeat waste earned 133.29%. The feasibility of sawdust waste was 2.41 while cocopeat waste was 2.33 as well. Otherwise, the cocopeat waste medium was higher 99.21IDR than sawdust waste in cost/kg yield. Net income using cocopeat waste medium was 2,739,694.50IDR, and cocopeat waste was 2,511,769.50IDR on average. Both cocopeat waste and sawdust waste medium are very feasible to be an agribusiness. The consideration is that the availability surrounds the production site, and cocopeat waste is cheaper than sawdust waste. Agribisnis jamur tiram (Pleurotus ostreatus) semakin diminati oleh karena permintaan terus meningkat. Kandungan gizinya lengkap dengan protein yang tinggi. Bahkan bagi vegetarian menjadi pengganti protein hewani. Media pertumbuhan jamur tiram biasanya menggunakan limbah serbuk gergaji. Media limbah serbuk sabut kelapa merupakan inovasi baru. Penelitian ini ingin mengetahui biaya-biaya hingga kelayakan usaha agribisnis jamur tiram menggunakan media limbah serbuk sabut kelapa dan yang biasa yaitu limbah serbuk gergaji Ternyata, Biaya total setahun menggunakan media limbah serbuk sabut kelapa lebih hemat Rp750.000 dibandingkan dengan media limbah serbuk gergaji. Biaya per kilogramnya sedikit lebih mahal Rp99.21 tetapi hasil panen lebih rendah dari limbah serbuk gergaji. Jamur tiram media limbah serbuk sabut kelapa memberikan keuntungan 133.29% dan media limbah serbuk gergaji 140.72%. Jamur tiram media limbah serbuk gergaji memberikan keuntungan bersih/bulan rata-rata Rp2,739,694.50, sedangkan media limbah serbuk sabut kelapa rata-rata Rp2,511,769.50.Kedua media untuk jamur tiram sangat layak diusahakan dengan R/C ratio 2.33 dan 2.41. Pengusaha bisa mempertimbangkan media limbah serbuk sabut kelapa atau limbah serbuk gergaji tergantung ketersediaan di sekitar lokasi dengan informasi harga limbah sabut kelapa lebih murah daripada limbah serbuk gergaji.